2019
DOI: 10.4102/ajcd.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Employer requirements and employability mindsets influencing graduate workers’ self-confidence in gaining employment

Abstract: Background:Little is known about when (under which mindset conditions) graduate workers' self-confidence in gaining employment increases. Objective:The current study explored the interaction effects between employers' importance attached to graduate workers' graduateness and employability qualities, and graduate workers' mindsets of marketability, entrepreneurial orientation and networking or job search orientation in predicting their self-confidence in gaining employment. Method:The study was exploratory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The triarchic model of distance learning 'World of work competency' refers to employees' selfefficacious business acumen, leadership skills, information retrieval, numeracy, communication and critical thinking skills and capability for the multidisciplinary problem solving of complex business problems (business ingenuity). Individuals' sociodigital agility involves their self-efficacious inter-digital competency relating to digital collaboration for problem solving, managing socio-cultural diversity and selfdirected management of their own career and employability (Coetzee et al, 2019(Coetzee et al, , 2021Kohl & Swartz, 2019).…”
Section: World Of Work Orientationmentioning
confidence: 99%
“…The triarchic model of distance learning 'World of work competency' refers to employees' selfefficacious business acumen, leadership skills, information retrieval, numeracy, communication and critical thinking skills and capability for the multidisciplinary problem solving of complex business problems (business ingenuity). Individuals' sociodigital agility involves their self-efficacious inter-digital competency relating to digital collaboration for problem solving, managing socio-cultural diversity and selfdirected management of their own career and employability (Coetzee et al, 2019(Coetzee et al, , 2021Kohl & Swartz, 2019).…”
Section: World Of Work Orientationmentioning
confidence: 99%
“…Numerous literature is found on the associations between employment and other factors such as self-confidence, self-efficacy, personality attributes and quality of qualifications (Beaumont, Geyde & Richardson, 2016;Dacre Pool & Sewell, 2007;Finch et al, 2016;Kim, Kim & Lee, 2015;Onyishi et al, 2015). Coetzee, Ferreira and Potgieter (2019) confirmed that more research is needed on individuals' perceptions about the employability competencies needed to find suitable employment within the new digital world of work. Zakaria and Alhassan (2019) raised the critical question that if students perceive that their qualifications are preparing them adequately for the digital work world, will it enhance their sense of employability competency?…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, graduates tend to be committed and perform better when given difficult tasks . Coetzee et al (2019) state that when graduates apply self-management strategies, they are able to perform under pressure, adapt to challenges, monitor their own career development and learn new skills that they can apply to their activities. Self-management strategies can assist graduates to achieve their career goals and change their behaviour in order to achieve these (Maria, 2015).…”
Section: Self-management Strategies and Graduatesmentioning
confidence: 99%
“…According to Harvey (2001), graduates are employed for their ability to learn quickly, their innovative thinking and the knowledge they contribute to the organisation. Graduates are educated, quick at acquiring new knowledge, have the necessary qualifications, skills and knowledge and have the attitudes to solve work challenges (Adams & De Kock, 2012;Coetzee, Ferreira, & Potgieter, 2019). They therefore become valued employees for organisations (Coetzee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation